Global Philadelphia : immigrant communities old and new - Takenaka, Ayumi; Osirim, Mary Johnson (Philadelphia voices, Philadelphia visions., 2010)
The racial and ethnic composition of Philadelphia continues to diversify as a new wave of immigrants-largely from Asia and Latin America-reshape the city's demographic landscape. Moreover, in a globalized economy, immigration is the key to a city's survival and competitiveness. The contributors to Global Philadelphia examine how Philadelphia has affected its immigrants' lives, and how these immigrants, in turn, have shaped Philadelphia. Providing a detailed historical, ethnographic, and sociological look at Philadelphia's immigrant communities, this volume examine.